2020
DOI: 10.1002/vms3.242
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dynamics of cloned Mexican bighorn sheep embryos using morphological quality standards

Abstract: The developmental dynamics of cloned Mexican bighorn sheep ( Ovis canadensis mexicana ) embryos were evaluated based on morphological quality standards. Categories determined by standards were correlated with the embryonic development stage, number of nuclei and viability. The results showed no differences in the blastocyst rate between the experimental (cloned Mexican bighorn sheep embryos) and control (parthenogenetic domestic sheep embryos) groups ( p > .05), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The future studies at our laboratory may decipher some of these questions in order to thoroughly elucidate the importance of FOLR1 as a pivotal biomarker suitable for prediction of augmented susceptibility of embryonic genomes to efficient epigenetic reprogramming of their transcriptional activities. The latter could enable the embryologists to estimate the increased developmental competences and molecular quality of caprine and other mammalian species embryos produced by such modern assisted reproductive technologies as microsurgical IVF by intracytoplasmic sperm injection (Kharche et al., 2016; Magata et al., 2019; Menéndez‐Blanco et al., 2020; Shirazi et al., 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al., 2021; Hernández Martínez et al., 2020; Samiec et al., 2019; Skrzyszowska & Samiec, 2020, 2021; Wiater et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hernández et al [47] reported a low number of nuclei (44.2 ± 9.9) present in parthenogenetic blastocysts of O. aries and in interspecies cloned blastocysts of O. aries and Ovis canadensis mexicana (46.7 ± 8.1 nuclei). Lorenzo-Torres et al [48] reported 122 nuclei in good-quality blastocysts produced by IVF.…”
Section: Effect Of Resveratrol On Embryo Qualitymentioning
confidence: 99%